MacBook Pro and MacBook Air - Hart-Davis, Guy. (Indianapolis : Visual, 2020)
The visual learner's ultimate guide to the MacBook Pro, MacBook Air and macOS Catalina Teach Yourself VISUALLY MacBook is your ultimate guide to getting up and running quickly with your new MacBook Pro or MacBook Air! Whether you're new to computers or transitioning from a PC, this graphics-heavy guide will show you everything you need to know to get the most out of your new laptop. Clear, step-by-step instructions walk you through each task, with screenshots that help you follow along with confidence. You'll learn how to manage files, work with macOS software, organize photos and media, set up email, access the internet, and adjust settings and preferences to make your MacBook work the way you work. You'll also explore the features that bring computing to a whole new level, including iCloud, FaceTime, the App Store, and so much more! The Mac has long inspired a legion of loyal fans, and you're about to find out why. From sleek design to intuitive interface, to an OS that just works, Apple has cornered the market on the high-end computing experience. The MacBook makes sublime computing portable, and this book shows you how to take advantage of all that your MacBook has to offer. MacOS Catalina gives you more of everything you love about Mac. Prepare yourself to experience music, TV, and podcasts in newly designed Mac apps. You can now enjoy your favorite iPad apps on Mac, and even extend your workspace and expand your creativity with iPad and Apple Pencil. Packed with new features and updates to the apps Apple users love, you can now take everything you do up the next level. Get acquainted with the latest macOS version Cataline, and its new features Perform everyday tasks quickly and easily Customize preferences and settings to suit your needs Download new apps, video chat, save to the cloud, and much more! No confusing tech-speak, no vague instructions, and no complex tangents into obscure tasks. This friendly guide is packed with screenshots, easy-to-follow instructions, and a practical sensibility; you're not launching the space shuttle, you just want to open your email. If you're ready to explore all that your MacBook can do, Teach Yourself VISUALLY MacBook is your ideal companion.
Organize Your Files with Tags -- Work with Zip Files -- Using the Trash -- Customize the Finder Toolbar -- Customize the Sidebar -- Configure Finder Preferences -- Chapter 6 Surfing the Web -- Open a Web Page -- Follow a Link to a Web Page -- Open Several Web Pages at Once -- Navigate Among Web Pages -- Return to a Recently Visited Page -- Play Music and Videos on the Web -- Set Your Home Page and Search Engine -- Create Bookmarks for Web Pages -- Using Reader View and Reading List -- Download a File -- Configure Safari for Security and Privacy -- Chapter 7 Sending and Receiving E-Mail
Print version record.
Set Up Your E-Mail Accounts
John Wiley and Sons
Keywords: Mac OS; Mac OS; MacBook (Computer); Laptop computers; MacBook (Ordinateur); Laptop computers; MacBook (Computer)